Treatment of aggression in conduct disorders in children and adolescents - Zagórski, Karol; Kozik, Mateusz; Skalska-Dziobek, Nina; Małagocka, Weronika; Chybowska, Karolina; Naruszewicz, Maria; Cetnarowski, Przemysław (Quality in Sport, 2025)
Introduction and purpose: Treatment of conduct disorders is complex, reflecting their combined etiology in organic developmental issues and improper environmental influences. Therefore therapy involves complex psychotherapeutic interventions, focusing not only on the individual, but also on his family system, and sometimes including drug treatment. The purpose of this work is to discuss the most effective treatment strategies for children with aggressive behavior. Material and method: The literature was reviewed in the Pubmed database, GoogleScholar, the positions of the Polish gynecological society with the use of keywords. State of knowledge: Interventions for children and adolescents prioritize education and psychotherapy, with limited risperidone use due to side effects. Alternatives include stimulants, alpha agonists, atomoxetine, and SSRIs. The article examines aggression in CD and ODD, comorbid disorders (ADHD, CU, DBDNS), and behavioral treatments, emphasizing differential diagnosis and management. Summary: First-line treatment involves optimizing pharmacotherapy, such as stimulants for ADHD with aggression, with risperidone as a secondary option. Further research and individualized approaches are needed to improve therapy.